Geochemical impact of injection of Eagle Ford brine on Hosston sandstone formation—Observations of autoclave water–rock interaction experiments. (September 2017) - Lu, Jiemin; Darvari, Roxana; Nicot, Jean-Philippe; Mickler, Patrick; Hosseini, Seyyed A.
Abstract: This study investigates water–rock interactions induced by brine injection into the Cretaceous clastic Hosston Formation in South Central Texas, a potential host formation for disposal of produced water from the Eagle Ford Shale during oil and gas extraction. The primary objectives of this experimental study were to (1) predict the geochemical reactions between the injected brine and the host formation during disposal operation, and (2) assess potential impact on flow properties of the host rock. The results provide important information of potential impact to injectivity and available methods to alleviate the problems if they occur during brine disposal. Five batch autoclave experiments were conducted to react an argillaceous sandstone of the Hosston Formation with a series of synthetic brines and the Eagle Ford brine for 3 weeks at 193 bar and 80 °C. To better identify mineral dissolution and precipitation, rock samples were ion-milled and examined using scanning electron microscopy (SEM) before and after the experiments. For each experiment, approximately 15 aqueous samples were taken with increasing time intervals from hours to days. Dissolution of anhydrite, which results in a rapid increase of SO4 and Ca concentrations in the solution of ∼500 ppm and ∼200 ppm respectively, is the most significant reaction. Small amounts of dolomite and K-feldspar were also dissolved to release Mg, Ca, K, and Si. Small amounts of iron hydroxides and kaolinite precipitated. Geochemical modeling is able to reproduce the behavior of the major aqueous components and of the observed mineral dissolution and precipitation. Overall, change in flow properties from the water–rock interaction is insignificant: mercury intrusion capillary pressure (MICP) data show little difference in porosity, permeability, and pore-throat-size distribution between the pre- and post-experiment samples. This study suggests that injection of Eagle Ford brine into the Hosston Formation will pose minimum risks for the brine disposal operation. Highlights: Geochemical impacts of injection of Eagle Ford brine into Hosston sandstone for brine disposal are investigated. Hosston sandstone was reacted with synthetic brine and Eagle Ford brine in autoclave experiments. Aqueous chemistry and SEM comparison show anhydrite dissolution, mild dolomite dissolution, and small amounts of precipitated clay and iron hydroxides. Geochemical interactions caused little changes to rock properties.